2013
DOI: 10.1002/cncr.27871
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in regulator of G‐protein signaling (RGS) confer risk of bladder cancer

Abstract: Background Alterations in the RGS pathway have been implicated in several cancers; therefore, we determined their role in overall bladder cancer risk, recurrence, progression and survival. Methods This is a case-control series of 803 bladder cancer patients with a frequency-matched cohort of 803 healthy individuals. We evaluated 95 SNPs in 17 RGS genes for association with overall bladder cancer risk, recurrence and progression in patients with non-muscle invasive bladder cancer (NMIBC), and death in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In accordance with the original study, we observed a recessive association with OS in MIBC for rs12035879 [A] in RGS5 (HR = 2.79 [95% CI: 1.40–5.56]) and rs2075786 [A] in TERT (HR = 1.93 [95% CI: 1.01–3.68]) ( Tables 3 , 4 ) [ 13, 22 ]. For three of the other 42 evaluated SNPs ( i.e.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with the original study, we observed a recessive association with OS in MIBC for rs12035879 [A] in RGS5 (HR = 2.79 [95% CI: 1.40–5.56]) and rs2075786 [A] in TERT (HR = 1.93 [95% CI: 1.01–3.68]) ( Tables 3 , 4 ) [ 13, 22 ]. For three of the other 42 evaluated SNPs ( i.e.…”
Section: Resultssupporting
confidence: 89%
“…Among the 23 tested SNPs, only rs3795617 ( RGS13 ) was associated with NMIBC recurrence at the p < 0.05 threshold (CT/TT vs. CC: hazard ratio [HR] = 1.26 [95% CI: 1.04–1.53]), but with conflicting direction of effect compared to the original study ( Tables 3 , 4 , S1) [ 13 ]. Borderline significant evidence (0.05 < p < 0.10) for a directionally consistent association with recurrence was demonstrated for rs1800795 ( IL6 ) and rs25487 ( XRCC1 ) [ 14, 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inconsistency in direction of the effect was observed for SNPs in EGFR and RGS5 [HR = 1.5 (1.0–2.3) for rs2293347 (15) and HR = 1.55 (1.15–2.11) for rs2344673 (16)].…”
Section: Resultsmentioning
confidence: 99%
“…Cases were recruited from The University of Texas MD Anderson Cancer Center and Baylor College of Medicine as a part of an ongoing bladder cancer case control study since 1999. As described previously [ 55 ], cases were all newly diagnosed, histologically confirmed, and previously untreated with chemotherapy or radiotherapy at the time of recruitment. Controls were healthy individuals without prior cancer history (except for non-melanoma skin cancer) and were recruited through Kelsey-Seybold Clinics, the largest multispecialty physician group in the Houston metropolitan area.…”
Section: Methodsmentioning
confidence: 99%